Characteristics of Gipang, a traditional food of Baduy Tribe, Added with Milkfish Bone Flour to Improve Calcium and Phosphor Content - Baity Nur Jannah; Fitria Riany Eris; Nita Kuswardhani; Aris Munandar (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightMilk fish (Chanos chanos) bone flour to improve nutrition of GipangChemical, physical, and organoleptic characteristics of Gipang were analysedThe best concentration of milkfish bone added in gipang was 10%AbstractGipang is a well-known traditional food of Baduy, a local tribe located in Banten Province, West Java, Indonesia. This study aimed at the characterization of the traditional food with an addition of milkfish bone flour at four different concentrations. The study used a completely randomized design (CRD) with a single facto (concentration of milkfish bone flour addition). The addition of milkfish bone flour consisted of four levels, which were 0% as the control, 5%, 10%, and 15% of the weight of raw white glutinous rice used in the present study. Each treatment had 3 (three) replicates. During the experiment, the observed parameters were proximate analysis, calcium content, phosphors content, hardness, total valuable count (TVC) of microbes, and organoleptic characteristics (colour, taste, scent, texture, overall). Fishbone flour is processed from milkfish bone waste that obtained from the milkfish satay industry in Banten province. The addition of milkfish bone flour had a significant effect on ash, protein, fat, calcium, and phosphor contents, hardness, total microbes, and organoleptic properties of colour, taste, and overall values. The result showed that the best concentration of milkfish bone flour addition to the Gipang was 10% which had content characteristic respectively as follows: moisture 6.74%; ash 2.61%; protein 5.71%; fat 21.84%; carbohydrate 63.10%; calcium 3.68%; and phosphor 1.39%; hardness of 324.39 g/mm; TVC of microbes was 1.79 log10 CFU/ml; and organoleptic of colour 4.56; scent 4.40; taste 5.16; texture 5.08; and overall value of 5.28